1-Methylcyclopropene and Ethephon Effects on 'Carabao' Mango Fruits Harvested at Different Stages of Fruit Maturity - Manigo, Bryl; Antibo, Narlyn (Indonesian Journal of Agricultural Research, 2022)
Three experiments were conducted using three different stages of fruit maturity (100, 105, and 110 DAFI or days after flower induction) of ‘Carabao’ mangoes harvested from the same set of trees. Fruits harvested were applied with 1-MCP [(dosage:0.5 µL/L) via gas exposure for 20 hours and spraying], and ethephon (dipping at 1ml/L of H2O) applied singly or in combination. Mangoes were then stored in ambient room conditions [29.2±1.6°C, 69.88±4.0% relative humidity (RH)]. Mango fruits with 1-MCP treatment applied through gas exposure at 0.5 µL/L consistently delayed the peel color change, firmness, and weight loss of harvested fruits at 100, 105 and 110 DAFI. These fruits held its shelf life for 15 (100 DAFI), 12 (105 DAFI) and 9 (110 DAFI) days compared to control with 12, 10 and 8 days respectively. Furthermore, all treatments showed varied effects on the visual quality of fruits regardless of its maturity. It also appeared that fruits at 105 DAFI treated with ethephon alone have better taste while other organoleptic attributes, chemical properties (TSS, TTA and pH), as well as the disease incidence and severity were found to be comparable. This further proved that 1-MCP delays ripening of fruits but could not prevent disease occurrence.